2015
DOI: 10.1186/s12284-015-0041-x
|View full text |Cite
|
Sign up to set email alerts
|

Upstream regulatory architecture of rice genes: summarizing the baseline towards genus-wide comparative analysis of regulatory networks and allele mining

Abstract: Dissecting the upstream regulatory architecture of rice genes and their cognate regulator proteins is at the core of network biology and its applications to comparative functional genomics. With the rapidly advancing comparative genomics resources in the genus Oryza, a reference genome annotation that defines the various cis-elements and trans-acting factors that interface each gene locus with various intrinsic and extrinsic signals for growth, development, reproduction and adaptation must be established to fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 231 publications
(244 reference statements)
1
5
0
6
Order By: Relevance
“…Expression of SA related genes in both rice NILs appears to be a general response to pathogens, which is enhanced by high temperature in the resistant plant. Salicylic acid has numerously been reported to play an important role in resistance against pathogens [54][55][56][57][58][59][60] .…”
Section: Discussionmentioning
confidence: 99%
“…Expression of SA related genes in both rice NILs appears to be a general response to pathogens, which is enhanced by high temperature in the resistant plant. Salicylic acid has numerously been reported to play an important role in resistance against pathogens [54][55][56][57][58][59][60] .…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies in Nipponbare showed that the mechanisms associated with early defenses to cold involve three sequentially expressing regulons 17 , 20 , 21 , 45 . First is the oxidative-mediated regulon involving bZIP -TGA-type transcription factors binding to the as1/ocs-like cis-elements.…”
Section: Discussionmentioning
confidence: 99%
“…Cis-element spatial maps were visualized using the Matlab version R2017a ( http://www.mathworks.com ). Baseline annotation of all putative cis-elements in PLACE database 58 was further elaborated with additional information from the literature 29 , 45 .…”
Section: Methodsmentioning
confidence: 99%
“…O processo de regulação gênica pode ser dividido em diferentes etapas que envolvem desde a acessibilidade do DNA genômico até o processamento pós transcricional do gene [Ladunga, 1.2 2010, Levo and Segal, 2014, Villar et al, 2014. Entre estes mecanismos podemos destacar os realizados pelos Fatores de Transcrição (Transcription Factor -TF), a remodelagem do Nucleossoma, a ação de microRNAs, as alterações químicas na estrutura das Histonas e por fim a região Promotora [de los Reyes et al, 2015, Holoch and Moazed, 2015, Keung et al, 2015, Watson et al, 2015.…”
Section: Regulação Gênicaunclassified
“…Na ausência do complexo transcricional a RNA pol II não poderá transcrever o mRNA da sequência de DNA codificante que fica à jusante da região Promotora. Além disso, qualquer erro durante a montagem do complexo transcricional influenciará diretamente a transcrição do gene [de los Reyes et al, 2015, Rombauts et al, 2003]. Portanto, a região Promotora pode determinar de forma direta a quantidade, o tipo e o período de produção dos transcritos [Mejía-Guerra et al, 2015, Yamamoto et al, 2009.…”
Section: Região Promotoraunclassified